Karakteristik Pasangan Usia Subur yang Menggunakan Metode Kontrasepsi Jangka Pendek di Kecamatan Banjarmasin Tengah - Nurfiqria Hikmah; Deasy Arisanty; Karunia Puji Hastuti (Pendidikan IPS FKIP ULM, 2022)
This study aims to determine the demographic factors of short term contracepcion methods in fertile age couples in Banjarmasin Tengah District, Banjarmasin City, South Kalimantan Province in 2019. The research sample was fertile age couples who used short term contraception totaling 364 people. This study used descriptive research with a quantitative approach. Data collection was carried out using questionnaires, observations, interviews and studies of secondary data from related agencies. The sampling technique in the study used the Simple Random Sampling technique. Analyzing data in the study was descriptive analysis by percentage. The results showed that the fertile age couple in Banjarmasin who used short-term contraceptive methods were aged 20-35 years (61%), the number of children <2 (66%), high education level (66%), good contraception knowledge ( 100%), KIE from midwives (46%), family planning services from puskesmas (50%), and income according to the Banjarmasin UMR (58%). Keywords: Fertile age couple, short-term contraceptives, family planning, number of children